A study on Vietnamese - English translation of construction texts - Lương, Thị Ngân (University of Languages and International Studies, 2017)
This thesis focuses on Vietnamese – English translation of construction texts, an important and interesting field of translation. It aims at investigating the fundamental aspects in translation of construction texts, specifically lexical items and syntactic features. The study starts with the theoretical background which elaborates on the notion of translation, translation methods as well as translation procedures and equivalence. Then it touches upon the characteristics of technical translation and typical features of construction texts. In the main part, a detailed investigation and examination of the translation of lexical items and syntactic features in construction texts is carried out, from which it identifies the problems related and their major causes to find the suggested for solutions. The results of the study can be of some help to people who are working in translation area, especially in translation of construction field.